EFFORTS TO IMPROVE CHILDREN'S ABILITY TO EXPRESS OPINIONS THROUGH STORYTELLING AT SWAN NATIONAL SCHOOL PELEMWATU - Kezia, Deswenda (USN Kolaka, 2023)
Expressing opinions is one of the activities in kindergarten to develop children's basic abilities. The aim of this research is to find out whether storytelling in learning can improve the ability to express opinions of children in group A of the Swan National School Kindergarten. This activity uses the Classroom Action Research (PTK) method which is divided into 2 cycles with each cycle lasting 5 days. In improving the learning, 17 students in group A of the Swan National School Kindergarten were observed, they were motivated to be able to express their opinions through storytelling activities. The results obtained from all 17 Swan National School Kindergarten group A students in cycle I showed that there were 7 children who achieved very good development, and 6 children developed according to expectations. In the second cycle, improvement results were obtained, namely 11 children developed very well and 4 children developed as expected. Based on the data obtained, there was an increase in the ability to express opinions in group A of the Swan National School Kindergarten, namely from 76.5% in cycle I to 86% in cycle II, so it can be concluded that through storytelling activities it was quite successful in increasing children's ability to express opinions. Therefore, this research was carried out in only two cycles, in order to maximize storytelling activities, so that the ability to express opinions can achieve satisfactory results. Apart from that, it is hoped that teachers will be more creative in finding fun teaching methods and in the end learning objectives can be achieved.Â